Evaluation of the effectiveness of Washington State’s digital COVID-19 exposure notification system over one pandemic year - Elder, Adam S.; Arrouzet, Cory J.; Miljacic, Ljubomir; Karras, Bryant T.; Higgins, Amanda; West, Laura M.; Lorigan, Daniel; Revere, Debra; Polissar, Nayak; Segal, Courtney D.; Lober, William B.; Baseman, Janet G. (Frontiers in Public Health, 2024)
Introduction: Digital exposure notifications are a novel public health intervention used during the COVID-19 pandemic to warn users of a possible COVID-19 exposure. We seek to quantify the effectiveness of Washington State’s digital exposure notification system, WA Notify, as measured by the number of COVID-19 cases averted during a one-year period. Methods: While maintaining individuals’ privacy, WA Notify collected data that could be used to evaluate the system’s effectiveness. This article uses these and other data and builds on a previous model to estimate the number of cases averted by WA Notify. Novel estimates of some model parameters are possible because of improvements in the quality and breadth of data reported by WA Notify. Results: We estimate that WA Notify averted 64,000 (sensitivity analysis: 35,000-92,000) COVID-19 cases in Washington State during the study period from March 1st, 2021, through February 28th, 2022. During this period there were an estimated 1,089,000 exposure notifications generated and 155,000 cases reported to WA Notify. During the last seventy-eight days of the study period the median estimated number of daily active users was 1,740,000. Discussion: We believe WA Notify reduced the impact of the COVID-19 pandemic in Washington State and that similar systems could reduce the impact of future communicable disease outbreaks.